COMPARISON AMONG DERMATOGLYPHICS, SPEED AND STRENGTH OF GIRLS FROM SETTLEMENT AND FROM URBAN PERIMETER IN BAHIA-BRAZIL (Fiep Bulletin - online, 2011)
The objective of the present study was compare the dermatoglyphic characteristic (A, L, W, D10 and TSLQ) and the physicals qualities (speed and strength) of girls from the settlements called Antônio Conselheiro and Rose, and from the urban perimeter of a brazilian city, which belongs to the State of Bahia, called Santaluz. The sample was based upon 18 girls from the settlements and 21 from the urban perimeter. The methodology: transversal study of descriptive and comparative approach; the t Test was utilized to compare the quantitative variables and the Mann-Withney Test to compare the qualitative one. The Dermatogliphia was utilized to determinate the dermatoglyphics characteristics; for testing speed the 30m dash has been utilized and strength was tested by the Sargent Jump Test. Girls have shown the following characteristics: (settlement /city) height (cm)=(141.1±5.9 / 144.8±7.22), body mass (Kg)=(32.4±5.3 / 36.6±7.6) and BMI (Kg/m2)= (16.3±1.9 / 17.3±2.4). The qualitative dermatoglyphics characteristics of the settlements have been: AL=33.3%, ALW=22.2%, 10L=5.6%, 10W=11.1%, L>W=1.1% and W>L=16.7%; of the city have been: AL=28.6%, ALW=14.3%, 10L=14.3%, L=W=4.8%, L>W=14.3%, W>L=14.3% and 10A=9.5%; the quantitative have been: D10=(11.1±5.09 / 9.3±5.01) and TSLQ=(100.3±56.09 / 95.8±53.55). The results of the physicals qualities tests have been following: strength (cm)=(28.08±3.85 / 26.81±4.14). A significative difference was found only in the result of the speed (sec)=(6.81±0.55 / 6.46±0.41*), p=0.0285. In the statistic treatment a level of significance has been adopted (p
Keywords: Dermatogliphia; speed; strength